Spaces of piecewise-continuous almost periodic functions in almost periodic sets on the line. II - Samoilenko , А. M.; Trofimchuk , S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The authors consider a series of spaces of piecewise-continuous almost periodic functions and study the properties of the elements of these spaces. The theory developed in the paper is then applied to investigate almost periodic linear pulse systems.